One rule for the goose, one for the gander?: wrongfulness and harmfulness in determining reactions to offenders and victims of crime - Lens, Kim M. E. (European journal of criminology, 2017)
People’s reactions to offenders and victims of crime follow different rationales. Whereas the punishment of the offender is primarily determined by the severity of the crime (which includes its foreseeable harmful consequences), the actual harm that is experienced by the victim drives the need for his or her support and assistance. With the introduction of the Victim Impact Statement (VIS), in which victims are allowed to express the (harmful) consequences of the crime on their lives, the question is raised whether allowing such victim input during criminal proceedings would influence the offender’s sentence. The main goal of the current research is to disentangle how a crime’s wrongfulness and harmfulness influence people’s reactions to offenders and victims. We show that, whereas people’s perceptions of the offender (and the outcome of the trial) are influenced by the severity of the crime, people’s judgements related to the victim are more likely to be influenced by an interaction between the severity of the crime and the experienced harm of the crime. That is, in this study no support was found for the argument that the delivery of a VIS would lead to a violation of the proportionality principle.